THE MODEL CONSTRUCTION OF OECD BASE EROSION PROFIT SHIFTING ACTION PLAN 12TH TO ACHIEVE TAX PLANNING TRANSPARENCY - Andang Wirawan Setiabudi; Christianus Yudi Prasetyo; Jesslyn Huberta Tanada (Jurnal Akuntansi, 2022)
This study presents ideas about the construction of policies under the authority of the Directorate General of Taxes (DGT) in response to recommendations issued by the OECD regarding how to deal with aggressive tax planning related to the current era of globalization. The tax avoidance practice is known as the Base Erosion and Profit Shifting (BEPS) which is allegedly rampant by taxpayers (WP), especially for the Multi National Company (MNC). The impact of the BEPS practice is the loss of state revenues experienced by almost every country, especially developing countries. This is a major concern for developing countries because tax revenues are an important component of government revenues to encourage development. The OECD BEPS action plan issued at the G20 meeting in Moscow Russia in July 2013 had 15 action plans. In this case, the Indonesian Government has not implemented all the recommendations for the OECD BEPS action plan. One recommendation that has not been made is the OECD BEPS action plan 12 concerning Mandatory Disclosure Rules (MDR). MDR here is about the disclosure of the company's strategies regarding tax planning. This is necessary because there must be tax planning transparency carried out by WP. This condition is closely related to Human Activity Systems, which are purposeful activities. Therefore the writer studied it with an action-based Soft Systems Methodology (SSM) approach with the category of research interest. Keywords: BEPS, aggressive tax planning, mandatory disclosure rules, action-based SSM, research interest